2020
DOI: 10.1101/2020.11.24.393405
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fragment Binding to the Nsp3 Macrodomain of SARS-CoV-2 Identified Through Crystallographic Screening and Computational Docking

Abstract: The SARS-CoV-2 macrodomain (Mac1) within the non-structural protein 3 (Nsp3) counteracts host-mediated antiviral ADP-ribosylation signalling. This enzyme is a promising antiviral target because catalytic mutations render viruses non-pathogenic. Here, we report a massive crystallographic screening and computational docking effort, identifying new chemical matter primarily targeting the active site of the macrodomain. Crystallographic screening of diverse fragment libraries resulted in 214 unique macrodomain-bin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
113
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(121 citation statements)
references
References 106 publications
(170 reference statements)
8
113
0
Order By: Relevance
“…Given the urgent need for antiviral therapies for COVID-19 and the fact that the macrodomain is an attractive therapeutic target (Alhammad & Fehr, 2020;Brosey et al, 2021;Rack et al, 2020;Schuller et al, 2020), we attempted to repurpose compounds that already have regulatory approval as potential Nsp3 macrodomain inhibitors. For this, we performed a structure-based virtual screen of a library of 6364 compounds that have been approved for human use by any regulatory agency in the world, against the deposited crystal structures of the SARS-CoV-2 Nsp3 macrodomain bound to ADP-ribose (PDB 6W02) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the urgent need for antiviral therapies for COVID-19 and the fact that the macrodomain is an attractive therapeutic target (Alhammad & Fehr, 2020;Brosey et al, 2021;Rack et al, 2020;Schuller et al, 2020), we attempted to repurpose compounds that already have regulatory approval as potential Nsp3 macrodomain inhibitors. For this, we performed a structure-based virtual screen of a library of 6364 compounds that have been approved for human use by any regulatory agency in the world, against the deposited crystal structures of the SARS-CoV-2 Nsp3 macrodomain bound to ADP-ribose (PDB 6W02) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Successful viral evasion or suppression of the host interferon response is key for the establishment of a viral infection and is often mediated by several viral factors acting on multiple host targets (Garcia-Sastre, 2017). The coronavirus Nsp3 macrodomain is thought to represent an important mediator of coronavirus pathogenesis by reversing host antiviral ADP-ribosylation and is thus an attractive drug target (Alhammad & Fehr, 2020;Brosey et al, 2021;Rack et al, 2020;Schuller et al, 2020). However, little is known about the molecular targets of IFN-responsive PARPs and how reversal of these modifications by the Nsp3 macrodomain may exert its pro-viral effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As this is also thought to be true of σ 1 ligands, and because most σ 2 ligands cross-react with the σ 1 receptor, probe ligands selective for σ 2 over σ 1 would help illuminate σ 2 biology and could be leads for novel therapeutics. However, given the relatively recent determination of the σ 2 receptor's molecular identity relatively little is known regarding its molecular architecture, ligand recognition, or amenability to methods like virtual screening for ligand identification [23][24][25][26][27][28][29][30] . Here, we employed a biochemical and structural approach combined with computational docking to address these issues.…”
Section: Introductionmentioning
confidence: 99%
“…This flexibility offers opportunities for rational targeting this protein module by small molecule inhibitors. Indeed, recent study has reported a number of potential small molecule binders discovered through crystallographic fragment screening 31 . In line with this, our unprecedented discovery of the binding of GS-441524, an active metabolite of remdesivir, supported this hypothesis that the ADP-ribose pocket of the macrodomain indeed represents a druggable site.…”
mentioning
confidence: 99%